PENGARUH PENDAPATAN KELUARGA TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN EKONOMI KELAS X TAHUN AJARAN 2016/2017 SMA NEGERI 1 BENAI - Kurnia, Shafiqa Putri; ', Sumarno; sabrus, Herdisyem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research in SMA Negeri 1 Benai to know the influence of Family income on student achievement of economic subjects class X academic year 2016/2017 SMA Negeri 1 Benai. The population in this study is all students of grade X SMA Negeri 1 Benai, amounting to 190 students. Sampling in this study was obtained using Area Probability Sample method of 66 students. . Technique of collecting is done through questionnaire technique and using primary and secondary. The data were analyzed by hypothesis using simple linear regression, partial test (t test), Coefficient of Determination (R2), and different test. There are 2 variables that is family income and student achievement.The results showed that family income variable effect student achievement. This means that the independent variables together affect the dependent variable. Furthermore, based on partial test (t test) it can be seen that only family income variable that affect student achievement is shown with significance 0,417 while other variable haven no effect.Keywords : Family Income, Student Achievement.